An observational study on prevalence of skin diseases in psychiatric patients - Gupta, Gunjan; Akhoon, Neha; Sudan, Rahul; Rafiq, M.; Kaul, Rajiv (International Journal of Research in Medical Sciences, 2025)
Background: Skin diseases and psychiatric disorders are related to each other because of common ectodermal origin. The aim of this study was to study the prevalence and distribution of skin diseases in patients with primary psychiatric disorders. Methods: The 100 patients diagnosed with primary psychiatric disorders who gave consent were studied for dermatological diseases. Results: Of these 100 patients, 36 (36%) were diagnosed with schizophrenia, 24 (24%) with bipolar disorder, 14 (14%) with major depressive disorders, 14 (14%) with anxiety disorders and 12 (12%) with obsessive-compulsive disorder. Of these patients, 72 (72%) had dermatological disorders. Non-infectious dermatological disorders constituted 59.72% of the total skin diseases and infectious 40.28% of the total patients. Amongst non-infectious dermatoses, eczematous disorders were most prevalent (13.88%), while amongst infectious dermatoses, folliculitis and furunculosis were most commonly encountered (9.72% each). Conclusions: Infectious and non-infectious skin diseases were common in patients with primary psychiatric diseases.